Comparative Effects of Verapamil, Nicardipine, and Nitroglycerin on Myocardial Ischemia/Reperfusion Injury - Hitoshi Yui; Uno Imaizumi; Hisashi Beppu; Mitsuhiro Ito; Munetaka Furuya; Hirofumi Arisaka; Kazu-Ichi Yoshida (Anesthesiology Research and Practice)
The aim of this experiment was to establish whether verapamil, nicardipine, and nitroglycerin have (1) infarct size-limiting effects and (2) antiarrhythmic effects in in vivo rabbit hearts during ischemia/reperfusion. Rabbits received regional ischemia by 30 min of left anterior descending coronary artery occlusion followed by 3 hours of reperfusion under ketamine and xylazine anesthesia. The animals were randomly assigned to the following 4 treatment groups: a control group, a verapamil group, a nicardipine group, and a nitroglycerin group. A continuous infusion of verapamil, nicardipine, or nitroglycerin was initiated 5 min prior to ischemia. Infarct size/area at risk decreased in verapamil, and nitroglycerin. The incidence of ischemia-induced arrhythmia decreased in nicardipine, verapamil and nitroglycerin. The incidence of reperfusion-induced arrhythmias decreased in verapamil and nitroglycerin. From the present experimental results, verapamil and nitroglycerin rather than nicardipine did afford significant protection to the heart subjected to ischemia and reperfusion in a rabbit model.